Product Quality Control Analysis with Statistical Process Control (SPC) Method in Weaving Section (Case Study PT.I) - Yusita Attaqwa; Aqidatun Hamidiyah; Firman Ardiansyah Ekoanindyo (International Journal of Computer and Information System (IJCIS), 2021)
Abstract - PT.I is a company that produces synthetic rattan furniture on an export scale. The various products at PT.I are an attraction for consumers, such as classic and modern weaving models. However, the number of defects produced is higher than the tolerance limit company. Based on data from the weaving section, it shows that there are 5 types of defects that are not in accordance with the standards and quality that have been determined by the company. The purpose of this study is to identify the types of defects that often occur in PT. I and identify the main factors causing product defects using the SPC method. The seven tools consist of a check sheet, histogram, stratification, scatter diagram, p control chart, Pareto diagram, and fishbone diagram. The results showed that the number of defects in October and November exceeded the limit set by the company. The highest level of disability occurred in October. The higher the number of production, the higher the number of product defects. Based on the results of the p control chart, it can be seen that the product is outside the control limits that it should have. The process is in a state of uncontrollability or is still experiencing deviations. To suppress or reduce the number of product defects that occur in production, 3 types of dominant defects can be applied, namely the woven model (254 units), loose woven (122 units), and nail-looking woven (119 units). Factors causing defects in production are derived from human factors/workers, methods, materials/raw materials and work environment.